Neuroplasticity of Sensory and Sympathetic Nerve Fibers in the Painful Arthritic Joint - Ghilardi, Joseph R. (2012)
OBJECTIVE: Many forms of arthritis are accompanied by significant chronic joint pain. Here we studied whether there is significant sprouting of sensory and sympathetic nerve fibers in the painful arthritic knee joint and whether nerve growth factor (NGF) drives this pathological reorganization. METHODS: A painful arthritic knee joint was produced by injection of complete Freund’s adjuvant (CFA) into the knee joint of young adult mice. CFA-injected mice were then treated systemically with vehicle or anti-NGF antibody. Pain behaviors were assessed and at 28 days following the initial CFA injection, the knee joints were processed for immunohistochemistry using antibodies raised against calcitonin gene-related peptide (CGRP; sensory nerve fibers), neurofilament 200 kDa (NF200; sensory nerve fibers), growth associated protein-43 (GAP43; sprouted nerve fibers), tyrosine hydroxylase (TH; sympathetic nerve fibers), CD31 (endothelial cells) or CD68 (monocytes/macrophages). RESULTS: In CFA-injected mice, but not vehicle-injected mice, there was a significant increase in the density of CD68(+) macrophages, CD31(+) blood vessels, CGRP(+), NF200(+), GAP43(+), and TH(+) nerve fibers in the synovium as well as joint pain-related behaviors. Administration of anti-NGF reduced these pain-related behaviors and the ectopic sprouting of nerve fibers, but had no significant effect on the increase in density of CD31(+) blood vessels or CD68(+) macrophages. CONCLUSIONS: Ectopic sprouting of sensory and sympathetic nerve fibers occurs in the painful arthritic joint and may be involved in the generation and maintenance of arthritic pain.